A man with recurrent axillary abscess - Durmaz, Gamze; Beycan, Esin; Kaya, Abdurrahman; Mert, Ali (My University, 2025)
...
Un hombre con absceso axilar recurrente
Keywords: Amoxicillin Plus Clavulanic Acid; C Reactive Protein; Ciprofloxacin; Hemoglobin